Changing party coalitions : the mystery of the red state-blue state alignment - Hough, Jerry F., 1935- (Agathon, 2006)
Where did the so-called Red states and Blue states come from? Prof. Jerry F. Hough observes that the historic Democratic-Republican party alignment was based on the great conflict between the North and the South, which itself was based and on the hostile European-American races. Both of these conflicts basically ended in the 1960s and 1970s as European-Americans became whites. This made a party realignment inevitable, but the politics surrounding the conflicts made it difficult to understand what was happening. As a result, the political elites crafted a highly unnatural and unhealthy red state-blue state alignment. This political reality is not incorporated in the theories of comparative politics and of nation-building, Hough explains, because it has been too encased in this mythology. The 1950s through the 1970s was a period of great political turmoil in the United States. The dramatic events of the black revolution, the anti-Vietnam demonstrations and the women's liberation movement caught everyone's attention, but some of the most fundamental changes were less visible. The book, based in substantial part on archival work, breaks outmoded taboos on the American past. The relations between North and South were highly confrontational, but the period actually led to the end of the historic North-South conflict that had defined the American political system since the Revolution. The two parties have been groping ever since to find a satisfactory new set of coalitions, but they have thus far failed. The new divide, the red state-blue state alignment, produces even narrower and more polarized electoral results in a society that is not fundamentally polarized. What is going on? The author insists that narrow cultural issues are used as electoral platforms in today's politics, not because of their inherent importance, but because of party strategies. He explains how we can return to the healthy debating role that a two-party system is supposed to play in a democratic nation and why this is so crucial.